Association Between Fentanyl Use and Post-Intubation Mean Arterial Pressure During Rapid Sequence Intubation: Prospective Observational Study - Abdullah Bakhsh; Ahmad Bakhribah; Raghad Alshehri; Nada Alghazzawi; Jehan Alsubhi; Ebtesam Redwan; Yasmin Nour; Ahmed Nashar; Elmoiz Babekir; Mohamed Azzam (Western Journal of Emergency Medicine)
Introduction: The choice of medications used in rapid sequence intubation (RSI) can result in the difference between an acceptable outcome and a lethal one. When executed properly, RSI is a lifesaving intervention. Nonetheless, RSI may result in fatal complications such as peri-intubation cardiac arrest. The risk of peri-intubation cardiac arrest reportedly increases in patients who are profoundly hypoxic or hypotensive prior to endotracheal intubation. Medication choice for RSI may either optimize or deoptimize hemodynamic parameters, thereby impacting patient outcomes. Therefore, our study aimed to examine the association of change in mean arterial pressure (MAP) with and without the use of a predetermined dose of 50 micrograms (μg) intravenous fentanyl as a pretreatment agent during RSI. Methods: This prospective observational study included patients undergoing RSI at an academic emergency department (ED) over a three-year period between January 1, 2018–January 1, 2021. Average hemodynamic parameters were measured at the time of induction (prior to medication administration) and 10 minutes after induction. We categorized patients into fentanyl and non-fentanyl groups for analysis, and we compared data using chi-square and t-test as appropriate. Logistic regression analysis was conducted to account for potential confounding factors. Results: A total of 278 patients were included in the analysis, of whom 160 received fentanyl and 118 did not. The majority of the patients underwent RSI by trainees 95.0% of the time. The first-pass success rate was 77.7% in our sample and did not differ significantly between the two groups (P = 0.84). Unadjusted analysis showed a larger decrease in hemodynamic parameters in the fentanyl group compared to the non-fentanyl group; systolic blood pressure decreased by 11.2% vs 1.6%, diastolic blood pressure decreased by 13.7% vs 3.8%, and MAP decreased by 12.7% vs 3.2%. After adjusting for potential confounders, fentanyl was 2.14 times more likely to lower MAP by 10%. Conclusion: The use of 50 μg fentanyl for rapid sequence intubation in an ED is associated with higher odds of decreasing mean arterial pressure by at least 10% at 10 minutes from the time of induction. Therefore, it should be carefully dosed, and its use in clinical practice should be justified to avoid unnecessary complications.